Removal of systematic failure of belt conveyor drive by reducing vibrations. (May 2019) - Homišin, Jaroslav; Grega, Robert; Kaššay, Peter; Fedorko, Gabriel; Molnár, Vieroslav
Abstract: The performance of continuous conveyor systems based on belt conveyors depends on their reliable and trouble-free operation. The most common failures encountered during their operation are mainly those directly related to the conveyor belt itself. However, this is not the only case that may cause their operation to be interrupted. A breakdown may also result from increased wear of the belt conveyor itself. Such systematic failure occurrence then greatly manifests itself in the reduced uptime of the entire belt conveyor. One of the effective solutions to the given problem is to make predictions of their emergence using dynamic models. By appropriately modified dynamic belt conveyor models, it is possible to quickly and accurately establish and predict the cause and location of the conveyor drive wear. This paper presents the belt drive upgrade has been verified under operating conditions. Trouble-free operation time, during which the online belt conveyor's technical condition was monitored, has increased 6 times in comparison to the original life of the drive. Highlights: Using simulation methods to identify causes of failure of belt conveyor drive On-line conveyor belt condition monitoring post upgrade 6-fold increase in the belt conveyor trouble-free operation